Resource conservation using whole body autophagy: Self-digestion of shedded gut lining cells in the small intestine - Lee, Phil Jun; Cho, Namki; Yoo, Hee Min; Chang, Sun Young; Ko, Hyun Jeong; Kim, Hong Pyo (Korean Journal of Food Science and Technology, 2020)
To retain valuable resources, organisms adopt several strategies including coprophagy. Cells covering the outer skin and internal digestive lumen are actively recycled to maintain their integrity. In present study, we suggested that the small intestine can consume dead cells in a manner similar to how it consumes protein from the diet. We examined the eluates from five segments of the mouse small intestine and cecum and 2 segments of the large intestine and small intestine tissue, and detected immunoreactivity with eukaryotic caveolin-1 and β-actin antibodies only in the cecum and 2 segments from the large intestine. Bacterial agitation of the mouse intestine with Shigella disrupted the architecture and absorptive function of the small intestine. Small intestine eluates were immunoreactive with murine caveolin-1 and contained heme as determined by dot blot analysis. We concluded that the body conserves resources in the small intestine by disposing of and recycling shedded cells.
Keywords: Autophagy; Caveolin-1; Heme; Resource conservation; Small intestine